ATTENUATION OF THE HAEMODYNAMIC RESPONSES ARISING OUT OF LARYNGOSCOPY AND ENDOTRACHEAL INTUBATION: A COMPARATIVE STUDY OF ESMOLOL, METOPROLOL AND DILTIAZEM. - DR. S. UMAMAHESHWARA RAJU; DR. KARUNA SREE P; DR.G.VIJAYALAKSHMI (International Journal of Pharma and Bio Sciences, 2013)
Maintenance of hemodynamic responses during laryngoscopy and tracheal intubation is a perpetual challenge for anaesthetists. The drugs commonly used to maintain the hemodynamic responses are ß-blockers, calcium channel and sodium channel blockers. To assess and compare the efficacy of Esmolol, Metoprolol and Diltiazem in controlling the hemodynamic responses. The study was conducted in the Dept. of Gynaecology, Gandhi Hospital, after the permission from Institutional Ethics Committee. Eligible Patients(N=75) were randomly enrolled into one of the three study groups(n=25). Each group received Esmolol, Metoprolol and Diltiazem respectively 3minutes before laryngoscopy and endotracheal intubation. Haemodynamic parameters i.e., Heart rate, Systolic, Diastolic, Mean arterial pressures and ECG were recorded before, during and after the intubation at 1, 3 and 5 minutes. Esmolol found to be more effective in suppressing the haemodynamic responses followed by Diltiazem and then by Metoprolol.